Evaluation of The Degree of Stress in First Year Students of The Faculty of Medicine, Muslim Indonesian University - Nurfauziah, Nurfauziah; Wahid, Syarifuddin; Mokhtar, Shulhana; Irmasanty, Irmasanty; Khaerina, Ilma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Stress is a phenomenon that often occurs in everyday life that cannot be avoided and can be experienced by everyone. There are so many demands in the first year of college that some students find them very heavy and difficult to fulfill. Students' failure to adapt to exams in the new academic year is likely to cause students to experience pressure. The research aims to determine the degree of stress and factors that trigger stress in first year students at the Faculty of Medicine, Indonesian Muslim University. This research is descriptive with a cross sectional method to measure stress levels based on stressors in first year medical students at the Faculty of Medicine, Muslim University of Indonesia, class of 2023. The method used is simple random sampling with a sample size of 295 first year students, class of 2023, Faculty of Medicine, Muslim University of Indonesia. The results of the research found that 295 students from the Faculty of Medicine, Indonesian Muslim University, class of 2023, on the Academic Related Stressor (ARS) factor, 130 people (44.1%) experienced a moderate level of stress, 152 people (44.1%) experienced a moderate level of stress on the Intrapersonal & Interpersonal Related Stressor (IRS) factor. people (51.5%), in the Teaching & Learning Related Stressor (TLRS) factor 121 people (41.0%) experienced a moderate level of stress, in the Social Related Stressor (SRS) factor 136 people (46.1%) experienced a moderate level of stress. Drive & Desire Related Stressors (DRS) experienced mild levels of stress as many as 168 people (59.9%), in the Group Activities Related Stressors (GARS) factor experienced moderate levels of stress as many as 123 people (41.7%). Based on the frequency distribution of stress levels, the number of stressors who experienced very severe stress was 35 people (11.9%).